Transcribing talk and interaction : issues in the representation of communication data - Jenks, Christopher Joseph (John Benjamins Pub. Co., 2011)
Interest in transcript-based research has grown significantly in recent years. Alongside this growth has been an increase in awareness of the empirical utility of naturalistic research on language use in interaction. However, a quick scan of the literature reveals that very few transcription books have been published in the past three decades. This is an astonishing fact given that there are perhaps hundreds of books published on spoken discourse analysis. This book aims to narrow this gap by providing an introduction to the theories and practices related to transcribing communication data. Th.